Ngobrol Pintar: A Community Service Program on Financial Literacy and Investment Awareness - Riady, Yasir; Pakpahan, Sondang Purnamasari; Marini, Yushita; Evriza, Eka; Marina, Nisha (PT Agung Media Publisher, 2025)
Financial literacy is a crucial competence in strengthening family financial planning and investment awareness. This community service program, Ngobrol Pintar (NGOPI), was initiated by Universitas Terbuka Medan in collaboration with Dharma Wanita Persatuan to address the need for accessible financial education in society. The program was implemented through an interactive seminar with 117 participants consisting of parents and children. The dialogue-based approach focused on gold investment as a practical entry point for understanding financial literacy. The seminar achieved active engagement from participants and increased awareness of financial management within the family context. Participants reported improved understanding of saving and investing practices, particularly related to gold as a long-term investment instrument. The findings indicate that financial literacy training through dialogue can effectively empower communities. Beyond a one-time session, the NGOPI initiative promotes sustainability by developing community-based financial literacy hubs, producing digital learning resources, and establishing partnerships with financial institutions and regulatory bodies. This approach positions financial literacy as an ongoing dialogue to build a culture of investment awareness and foster long-term financial resilience.